Simulasi Numerik Pengaruh Variasi Sudut Silinder Sirkular di Depan Returning Blade Terhadap Performa Turbin Angin Savonius Overlap - Naffatsa Alza Wiyoga; Priyo Agus Setiawan; Emie Santoso (Politeknik Perkapalan Negeri Surabaya, 2023)
Previous experiment has been carried out on Savonius wind turbine with additionaloverlap ratio and variation of circular cylinder stagger angle to improve its performance.However, the experiment didn’t show flow visualization around the turbine. Therefore,numerical simulation using Computational Fluid Dynamics (CFD) method must be carried outto validate the experiment result and obtain the best performance and flow visualization ofoverlap Savonius wind turbine. The turbine simulated has an overlap ratio of 0,3. Then, thecircular cylinder is placed in front of returning blade with a distance ratio (S/d) 1.7 andvarious stagger angle of 45 ?, 50 ?, 55 ? and 60 ?. The flow velocity used is 5 m/s. Turbulencemodel used in this simulation is k-epsilon realizable with transient pressure based. The finalresult is overlap Savonius wind turbine with circular cylinder has increased its performance of31,56 % compared with overlap Savonius wind turbine without circular cylinder. The bestperformance occurs at 55 ? circular cylinder stagger angle in front of returning blade with0,4118 Coefficient of Power (Cp) value. The flow visualization shows that 55 ? circular cylinderstagger angle is able to create the most optimum nozzle effect.